2020
DOI: 10.1177/2058739220960547
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, associated risk factors, and treatment of surgical site infections in Pakistan

Abstract: Globally, surgical site infections are one of the common infections which lead to a large amount of mortality and morbidity in postsurgical care. The risk for surgical site infection is multidimensional which includes mainly; patient, surgery, and hospital-related factors. This study is aimed to determine the burden of SSIs along with contributed risk factors. A prospective observational cross-sectional study was conducted in one of the largest public-sector hospitals in Pakistan. A total of 412 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…In contrast to our finding, a study was done by Khan UF in Pakistan (a part of the South-east Asian WHO region) have reported a slightly higher proportion of SSI (29.8%) among the patients who undergone seven different surgical procedures [43]. This emphasizes the importance of proper implementation of SSI preventive measures in these countries so that the additional burdens faced by the COVID-19 pandemic can be reduced.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to our finding, a study was done by Khan UF in Pakistan (a part of the South-east Asian WHO region) have reported a slightly higher proportion of SSI (29.8%) among the patients who undergone seven different surgical procedures [43]. This emphasizes the importance of proper implementation of SSI preventive measures in these countries so that the additional burdens faced by the COVID-19 pandemic can be reduced.…”
Section: Resultscontrasting
confidence: 99%
“…A WHO (world health organization) report revealed that out of a total of 67% of antibiotics used in the community about 30% are used irrationally by healthcare providers ( Koivusalo and Mackintosh, 2008 ). There is a direct link between the use of antibiotics and ABR and their use in the community ( Khan et al, 2020a ; Khan et al, 2021 ; Malik et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These determinants lead to the inappropriate use of antibiotics and, ultimately, antibiotics resistance is a likely the result of this misuse. Hence, there is an utmost need to engage the community and all stakeholders, including the local people, to stop the irrational use of antibiotics [24,[43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%